2022
DOI: 10.3390/catal12101096
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle–Hydrogel Based Sensors: Synthesis and Applications

Abstract: Hydrogels are hydrophilic three-dimensional (3D) porous polymer networks that can easily stabilize various nanoparticles. Loading noble metal nanoparticles into a 3D network of hydrogels can enhance the synergy of the components. It can also be modified to prepare intelligent materials that can recognize external stimuli. The combination of noble metal nanoparticles and hydrogels to produce modified or new composite materials has attracted considerable attention as to the use of these materials in sensors. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 121 publications
0
9
0
1
Order By: Relevance
“…Absorption of PANIs nanoparticles inside cPAM hydrogels during swelling in nanoparticle dispersions is a simple way to produce nanocomposites [ 78 ] ( Scheme 3 ). Typical cPAM hydrogels only permeate nanoparticles below 25–30 nm in diameter [ 79 ].…”
Section: Combination Of Polyacrylamides and Polyanilinesmentioning
confidence: 99%
“…Absorption of PANIs nanoparticles inside cPAM hydrogels during swelling in nanoparticle dispersions is a simple way to produce nanocomposites [ 78 ] ( Scheme 3 ). Typical cPAM hydrogels only permeate nanoparticles below 25–30 nm in diameter [ 79 ].…”
Section: Combination Of Polyacrylamides and Polyanilinesmentioning
confidence: 99%
“…[37] Hydrogels are a diverse and customizable class of materials, many of which have found applications in improving the function and biocompatibility of nanosensors. [38][39][40] Their chemical properties may be tuned to control their mechanical properties, porosity, biocompatibility, and other properties relevant to injection at numerous physiological locations. [37] They have such diverse applications as platforms for drug and cell delivery, cell recruitment, and as scaffolds for tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6]13,16,[33][34][35] Such hybrids with SWCNT and other nanomaterials-based sensors allow for more robust, long-term analyte detection as well as potentially improved sensitivity and specificity of the sensor. [38][39][40] Other studies have demonstrated impressive performance for surgically implanted hydrogel-encapsulated SWCNTs. Beyond preserving SWCNT fluorescence for 300 days, [5] multiple experiments have shown that hydrogels can reliably sequester SWCNTs without leakage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological activity of AgNPs is determined by their size, shape, and surface charge and is highly dependent on the technique used to prepare the nanoparticles. Because they combine the benefits of AgNPs and hydrogels onto a single platform, hydrogel-AgNPs composites have recently attracted significant interest in the biotechnological and biomedical domains as catalysts, sensors, antibacterial, and anticancer applications. Although there are many benefits from NPs, there are a few disadvantages, including aggregation and separation from the treated water in WWTPs.…”
Section: Introductionmentioning
confidence: 99%